Durability of feldspathic veneering ceramic on glass-infiltrated alumina ceramics after long-term thermocycling. - Mesquita, A. M.; Ozcan, M.; Souza, R. O.; Kojima, A. N.; Nishioka, R. S.; Kimpara, Estevão Tomomitsu [UNESP]; Bottino, M. A. (My University, 2010)
This study compared the bond strength durability of a feldspathic veneering ceramic to glass-infiltrated reinforced ceramics in dry and aged conditions. Disc shaped (thickness: 4 mm, diameter: 4 mm) of glass-infiltrated alumina (In-Ceram Alumina) and glass-infiltrated alumina reinforced by zirconia (In-Ceram Zirconia) core ceramic specimens (N=48, N=12 per groups) were constructed according to the manufacturers' recommendations. Veneering ceramic (VITA VM7) was fired onto the core ceramics using a mold. The core-veneering ceramic assemblies were randomly divided into two conditions and tested either immediately after specimen preparation (Dry) or following 30000 thermocycling (5-55 oC±1; dwell time: 30 seconds). Shear bond strength test was performed in a universal testing machine (cross-head speed: 1 mm/min). Failure modes were analyzed using optical microscope (x20). The bond strength data (MPa) were analyzed using ANOVA (α=0.05). Thermocycling did not decrease the bond strength results for both In-Ceram Alumina (30.6±8.2 MPa; P=0.2053) and In-Ceram zirconia (32.6±9 MPa; P=0.3987) core ceramic-feldspathic veneering ceramic combinations when compared to non-aged conditions (28.1±6.4 MPa, 29.7±7.3 MPa, respectively). There were also no significant differences between adhesion of the veneering ceramic to either In-Ceram Alumina or In-Ceram Zirconia ceramics (P=0.3289). Failure types were predominantly a mixture of adhesive failure between the veneering and the core ceramic together with cohesive fracture of the veneering ceramic. Long-term thermocycling aging conditions did not impair the adhesion of the veneering ceramic to the glass-infiltrated alumina core ceramics tested.
Keywords: glass; In Ceram Alumina; In Ceram Zirconia; In-Ceram Alumina; In-Ceram Zirconia; VITA VM7; ceramics; comparative study; dental bonding; denture; equipment; evaluation; heat; humidity; in vitro study; materials testing; randomization; shear strength; time; tooth prosthesis; Ceramics; Dental Bonding; Dental Porcelain; Dental Veneers; Equipment Failure; Glass; Hot Temperature; Humidity; Materials Testing; Random Allocation; Shear Strength; Time Factors